What’s Happening: A Magazine by 1960s-1970s Young New Yorkers - Fish, Amy (Journal of Juvenilia Studies)

(untitled) (International Society of Literary Juvenilia, 2026)
This Spotlight essay explores a recently acquired collection of writings and drawings by primarily Black teenagers in the late 1960s and early 1970s United States. Held by the Gottesman Libraries of Columbia University’s Teachers College, the papers of What’s Happening: An Independent Student Voice include twenty-two issues of a youth-produced magazine that circulated across and beyond New York City, as well as related correspondence and photographs. I discuss the magazine’s influence, the demanding process of its creation, and the heartfelt correspondence exchanged by its creators. Through a close reading of single contribution to What’s Happening, a 1968 comic by Robert Jackson, I explore how the magazine’s authors conceived of their own acts of creation and exchange.